Burden of Antibiotic Resistance in Bloodstream Infections - Adhikhari, Archana; Mishra, Ved Prakash; Parajuli, Pramila (SXC Journal, 2025)
Bloodstream infections (BSIs) are among the leading causes of morbidity and mortality worldwide. In developing countries, rising cases are driven by changing epidemiology, antibiotic resistance, lack of standardized treatments, and inadequate diagnostics, which contribute to an increased rate of BSI-associated mortality. The main objective of this research was to identify multidrug-resistant (MDR), methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase (ESBL) producing bacteria isolated from blood specimens. The cross-sectional study was conducted in Alka Hospital, Lalitpur, from April to October 2023. A total of 737 blood specimens from suspected BSI patients were inoculated on BACTEC 9050 and subcultured on Blood agar and MacConkey agar. Bacteria were identified based on colony morphology and biochemical tests, and then the antibiotic susceptibility pattern was determined using the Kirby-Bauer disk diffusion method following CLSI 2018. ESBL production was detected by screening and phenotypic confirmatory tests, and methicillin-resistant S. aureus (MRSA) was detected using a Cefoxitin disc. Out of 737 specimens processed, 52 (7.06%) were culture-positive, with 37 (71.15%) Gram-negative bacteria and 15 (28.85%) Gram-positive bacteria. A total of 70.27% of Gram-negative isolates and 73.33% Gram positive isolates were found to be multidrug resistant (MDR). A total of 29.73% Gram-negative bacteria and 20% Grampositive bacteria were phenotypically confirmed as ESBL producers. MDR and ESBL-producing strains limit the treatment options. Therefore, strict regulations on antibiotic prescription and sales, and increased public awareness of their proper use must be implemented to prevent ineffective use, misuse and overuse, which drive the emergence of drug-resistant bacteria and exacerbate antimicrobial resistance.